2011
DOI: 10.1177/0264619611415329
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and enablers for visually impaired students at a UK Higher Education Institution

Abstract: The present study explored the factors which represent barriers and enablers to participation in Higher Education for students who are visually impaired. Semi-structured interviews were conducted with nine visually impaired students who were studying at a Higher Education Institution in the United Kingdom. Interpretative Phenomenological Analysis revealed four higher-order themes: the student's attitude (i.e. self identity, positive aspects of being visually impaired, engagement with support), institutional pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 13 publications
1
40
1
1
Order By: Relevance
“…Results of a study conducted by Harris and Oppenheim (2003) in the UK showed that only 45.8% of the libraries in their study had specific features to assist visually-impaired students physically to access the library and its collections. Nevertheless, more recent studies in the USA and the UK have shown that great strides have been made to facilitate the accessibility of libraries to people with disabilities (Samson 2011, Bishop & Rhind 2011, Beaton 2005. The study by Samson (2011) found that, besides providing for most of the equipment required to facilitate accessibility to the library, authorities in 50% of the institutions provided disability parking near the library.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of a study conducted by Harris and Oppenheim (2003) in the UK showed that only 45.8% of the libraries in their study had specific features to assist visually-impaired students physically to access the library and its collections. Nevertheless, more recent studies in the USA and the UK have shown that great strides have been made to facilitate the accessibility of libraries to people with disabilities (Samson 2011, Bishop & Rhind 2011, Beaton 2005. The study by Samson (2011) found that, besides providing for most of the equipment required to facilitate accessibility to the library, authorities in 50% of the institutions provided disability parking near the library.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study by Samson (2011) found that, besides providing for most of the equipment required to facilitate accessibility to the library, authorities in 50% of the institutions provided disability parking near the library. Studies by Bishop and Rhind (2011) and Beaton (2005), both conducted in the UK, also showed that significant strides in facilitating access to people with disabilities had been made. Progress is indeed being made in developed countries towards making libraries accessible to people with disabilities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such initiatives, together with the significant legislative changes noted above, have contributed to the increasing number of disabled students in UK higher education (Department for Innovation, Universities and Skills, 2009; Equality Challenge Unit, ECU, 2015a) and prompted research specifically on the experience of disabled students; including in relation to the experience of students with different impairments (e.g. Bishop & Rhind, 2011) and their experience in different learning contexts, such as field trips (e.g. Hall, Healey & Harrison, 2002) and professional practice placements (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Access to the university is exacerbated by the barriers that have been experienced in compulsory education and baccalaureate and students usually end up in a complicated access to the labor market. These university students, as they explain [6], [7], [8] In the main barriers, we can mention the attitudinal, structural and organizational [4]. The majority of current studies coincide in identifying more obstacles than aids in the university trajectories of students with disabilities.…”
Section: Introductionmentioning
confidence: 91%